(untitled) (Annual of the Faculty of Philosophy in Skopje, 2014)
In this article it is presented the reversal theory viewpoint of stress (which draws distinction between four types of stress) and some of the strategies of coping. First, the main postulates of the theory are summarized. Here are considered the metamotivational modes of being and the concept of dominance. Additionally, a few empirical studies are presented which point out the differences of experiencing stress regarding the dominant metamotivational state. Finally; the conceptual definitions of the four types of stress are given and divers possibilities of coping.